L’UQAM, pionnière dans l’enseignement des relations publiques - Stéphanie Yates (Communiquer)
Public relations have been slow to establish themselves as a legitimate field of study in communications, partly because of the beginnings of the profession, marked by ethically questionable practices. Building on the theoretical developments of the 1980s, including James E. Grunig’s model of excellence in public relations, UQAM took the bold step of establishing, in the mid-1990s, the first program in North America entirely devoted to teaching public relations in French. From the outset, the program established close ties with practitioners; the Chaire de relations publiques et de communication marketing was created in this perspective. The research associated with this field of study will take off with the arrival of professors specializing, among other things, in risk and crisis communication, political communication, media strategies, discourse analysis, and the use of social media for public relations purposes. This research confers UQAM an important role in public relations study and a relevant reference for practitioners.